Pemberdayaan Masyarakat Pengrajin Nira Aren melalui Sosialisasi Diversifikasi Produk Berbasis Potensi Lokal untuk Mewujudkan Agribisnis Berkelanjutan - Moh Muchlis Djibran; Merita Ayu Indrianti; Aditya Djaini; Yusriyah Atikah Gobel; Ivan Taslim (Journal of Empowerment Community, 2026)
Empowering the economic community of Suka Makmur Village, Bone Bolang District, is a strategic step in supporting local independence and achieving sustainable development. One potential natural resource with high economic value that has not been optimized is palm sap. The palm sugar artisan community has so far focused on traditional palm sugar production, which, although a local characteristic, has not provided significant added value. Given this situation, this community service activity was carried out to introduce and socialize the concept of palm sap-based product diversification, emphasizing the potential for developing liquid palm sugar and palm syrup as innovations that are more adaptive to modern market needs. The implementation method was carried out in a participatory manner through socialization and counseling, accompanied by group discussions to explore opportunities, challenges, and market potential for palm sap derivative products. The results of the activity showed an increase in community understanding of product diversification, awareness of the importance of hygienic processing, and a collaborative spirit to continue innovation at the village level. This activity not only provided new insights to the community but also generated initial data on the palm sap value chain and production capacity that can be used as a basis for developing further programs. Thus, this program plays a role in strengthening sustainable local agribusiness systems through community empowerment based on local natural resource potential.